Abrupt shift of El Niño periodicity under CO 2 mitigation - Tomoki Iwakiri; Jong-Seong Kug; Fei-Fei Jin; Sen Zhao; Soon-Il An; Geon-Il Kim; Dongkyu Park (Proceedings of the National Academy of Sciences, 2025)
Removing CO 2 from the atmosphere is emerging as a viable strategy to mitigate global warming, yet the responses of the climate system to CO 2 reduction remain uncertain. One of the most uncertain aspects of El Niño behavior is the change in periodicity in response to CO 2 forcing [O. Alizadeh, Earth-Sci. Rev. 235 , 104246 (2022)]. In this study, we show that climate models consistently project an abrupt shortening of El Niño periodicity once CO 2 reductions commence in ramp-up and ramp-down CO 2 experiments. Besides the contribution of slow mean state changes, this phenomenon is shown to be driven by a southward shift of the Intertropical Convergence Zone (ITCZ) [J.-S. Kug, et al. , Nat. Clim. Chang. 12 , 47–53 (2022)] and the consequent narrowing of El Niño’s spatial pattern, which enhances the effectiveness of ocean heat recharge/discharge processes, thereby shortening its periodicity. This suggests that the abrupt shift in El Niño periodicity results from a cascading reaction involving ITCZ dynamics and El Niño’s spatial configuration. These findings highlight the critical role of the global energy balance in shaping El Niño characteristics.